Efektifitas Peraturan Daerah Kabupaten Banyuwangi Nomor 2 Tahun 2020 Tentang Penanggulangan Kemiskinan - Malik Syaifuddin (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2024)
This paper aims to assess the effectiveness of Banyuwangi Regency Regulation Number 2 year 2020 on Poverty Reduction. This regulation is an effort by the local government in addressing the problem of poverty in the region. This study was conducted through a document study approach. The results showed that the local regulations have some success in poverty reduction in Banyuwangi. This local regulation also encourages active community participation in poverty reduction efforts. Through extension and mentoring activities, communities are encouraged to engage in economic empowerment programs and improve their quality of life. However, this study also revealed some obstacles in the implementation of these local regulations. Based on the findings of the study, it is recommended that local governments continue to evaluate and improve the implementation of local regulations Banyuwangi Number 2 year 2020. Increased budget allocation and improved coordination between relevant agencies can be important steps in improving the effectiveness of poverty reduction programs. In addition, involving the community actively in the planning and implementation of programs also needs to be improved to ensure these programs are relevant and provide a significant impact in reducing poverty in Banyuwangi.